2013
DOI: 10.1002/grl.50570
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation causes different subregional effects on the Amazon bioclimatic equilibrium

Abstract: Deforestation on Amazonia and central Brazil Cerrado could change regional climate, possibly shifting forest equilibrium into a bioclimatic envelope typical of savannas. Although impacts of climate change induced by deforestation are likely to vary subregionally, the potential geographic variation of these effects and the thresholds of rainforest and Cerrado removal that will affect Amazonian bioclimatic equilibrium remain unknown. We evaluate the effects of deforestation scenarios of increasing severity on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 19 publications
3
50
0
2
Order By: Relevance
“…Any change in the original land use can result in significant alterations of the water balance components of a watershed. Hydrological modeling studies have demonstrated the impact of such changes on these components (Pires & Costa, 2013). Changes in the processes of evapotranspiration, soil water infiltration and runoff are the main consequences of land use changes in watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Any change in the original land use can result in significant alterations of the water balance components of a watershed. Hydrological modeling studies have demonstrated the impact of such changes on these components (Pires & Costa, 2013). Changes in the processes of evapotranspiration, soil water infiltration and runoff are the main consequences of land use changes in watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…A utilização do TRMM demostra que os dados estimados são boa alternativa para localidades em que se observa baixa densidades de pluviômetros, como é o caso de grandes bacias hidrográficas em que se emprega os dados estimados pelo TRMM como entrada em modelos hidrológicos (PIRES;COSTA, 2013;PAIVA et al, 2013;BUARQUE et al, 2011).…”
Section: Introductionunclassified
“…To explore this effect, we calculated how the Mean Annual Water Deficit (MAWD; see Methods) would change in the absence of forest-rainfall cascades. We find that the MAWD in the south-western Amazon would increase from 196 mm to 380 mm, suggesting that forest-rainfall cascades are indeed a major suppressor of forest fires in the south-western Amazon and may thus sustain a large portion of its tree cover (Pires & Costa, 2013;Zemp et al, 2017a). An issue of particular concern is the possibility that parts of the Amazon forest may undergo tipping points to a savanna state (Lenton et al, 2008;Nepstad et al, 2008;Malhi et al, 2009;Nobre & Borma, 2009;Pires & Costa, 2013).…”
Section: Resultsmentioning
confidence: 85%